The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0103522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fragmentation and Sea-Level Changes upon Frog Communities of Land-Bridge Islands off the Southeastern Coast of Brazil

Abstract: We investigate the composition of anuran communities of land-bridge islands off the southeastern coast of Brazil. These islands provide natural long-term experiments on the effects of fragmentation in the Brazilian Atlantic Forest (BAF). We hypothesize that Pleistocene sea-level changes, in combination with other abiotic variables such as area and habitat diversity, has affected anuran species richness and community composition on these islands. Data from the literature and collections databases were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 49 publications
(55 reference statements)
1
17
1
Order By: Relevance
“…NESTEDNESS AND COMMUNITY STRUCTURE.-We did not detect a nested pattern in the anuran communities studied, which contrasts with the nested structure found in other frog communities in islands (Yiming et al 1998, Hecnar et al 2002, Bittencourt-Silva & Silva 2014, ponds (Hecnar & M'Closkey 1997, Werner et al 2007, or forest fragments (Vallan 2000, Watling et al 2009). For example, in a study evaluating the tadpole communities in 37 ponds, those that were found in ponds with high canopy cover, small area, and short hydroperiod were nested subsets of those with contrasting characteristics (Werner et al 2007).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…NESTEDNESS AND COMMUNITY STRUCTURE.-We did not detect a nested pattern in the anuran communities studied, which contrasts with the nested structure found in other frog communities in islands (Yiming et al 1998, Hecnar et al 2002, Bittencourt-Silva & Silva 2014, ponds (Hecnar & M'Closkey 1997, Werner et al 2007, or forest fragments (Vallan 2000, Watling et al 2009). For example, in a study evaluating the tadpole communities in 37 ponds, those that were found in ponds with high canopy cover, small area, and short hydroperiod were nested subsets of those with contrasting characteristics (Werner et al 2007).…”
Section: Discussioncontrasting
confidence: 81%
“…, Hecnar et al . , Bittencourt‐Silva & Silva ), ponds (Hecnar & M'Closkey , Werner et al . ), or forest fragments (Vallan , Watling et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the western Caribbean, two species inhabit islands, Micrurus nigrocintus in the Greater Corn Islands and Corn Islands, east of Nicaragua and M. ruatans is the islands of Roatán, off the coast of Honduras (Crother, ), both these islands were connected to the mainland during the Pleistocene (Petuch, ; Woodburne, ). In South America, M. corallinus inhabits several coastal Brazilian islets (Cicchi, Sena, Peccinini‐Seale, & Duarte, ), which were connected to the mainland when sea level fell between 10–20 Kya (Bittencourt‐Silva & Silva, ; Bueno, Schmidt Dias, & Stelle, ; Violante & Parker, ). Hence, New World coral snakes seem to lack the long‐distance dispersal capabilities of other snakes (e.g.…”
Section: Discussionmentioning
confidence: 99%